The effect of friction spot stir welding in double rivet lap joint installation of aluminum 2024-T3 on the strength of shear tests - Ahmad imam Nawawi (Jurnal Polimesin, 2023)
The process of joining materials is very necessary to facilitate the manufacture of industrial products. Among these connections are rivets, bolts, nails, glue, and welding which is mostly done on metal materials. The aircraft skin is usually connected with rivets through a drilling process. Joining metal materials, especially aluminum, uses many welding techniques. The welding method currently being developed is Friction Stir Welding (FSW). FSW developed the Friction Stir Spot Welding (FSSW) process in joining metals, especially in this study using 2024-T3 aluminum. The purpose of combining the rivet method with FSSW is to see the material’s mechanical characteristics when applied to aluminum material. The FSSW method uses a 2500 RPM engine speed milling machine using a blunt tool holder with a pin dimension of 2.5 mm.  It is carried out using a pneumatic drill using a drill bit with a dimension of 2.5 mm. Aluminum 2024-T3 has of 200×20×2 mm dimensions, a hole spacing of 15 mm with double rivet lap joint installation. The results showed that the FSSW variation had a higher tensile shear strength of 2.8% than the drilling variation. However, the hardness value in the drilling variation is 56.3% higher than the FSSW variation in the Heat Affected Zone (HAZ). Microstructural observations also indicate differences in the HAZ region, where the FSSW is reduced in size and longer. This is due to the heat treatment process due to friction between the pin tool and the aluminum, thus changing the structure.